On one direct method for the approximate solution of a periodic boundary-value problem - Azizov, M. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We propose a direct method for the approximate solution of integral equations that arise in the course of approximate solution of a periodic boundary-value problem for linear differential equations by the method of boundary conditions. We show that the proposed direct method is optimal in order.